2013
DOI: 10.1063/1.4798248
|View full text |Cite
|
Sign up to set email alerts
|

Optical in situ monitoring of hydrogen desorption from Ge(100) surfaces

Abstract: Reactive scattering of H2 from Cu(100): Comparison of dynamics calculations based on the specific reaction parameter approach to density functional theory with experiment J. Chem. Phys. 138, 044708 (2013) Effect of transition-metal additives on hydrogen desorption kinetics of MgH2 Appl. Phys. Lett. 102, 033902 (2013) Writing charge into the n-type LaAlO3/SrTiO3 interface: A theoretical study of the H2O kinetics on the top AlO2 surface Appl. Phys. Lett. 101, 251605 (2012) Collective degrees of freedom inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Temperature-dependent measurements showed sensitivities of 10 17 /cm 3 at 400 C to 1 Â 10 18 /cm 3 at 600 C [42]. Recent work has also shown that RAS can be used to monitor the hydrogen termination of Ge during annealing in N 2 (Figure 29.19) [45]. Recent work by Bruckner et al [44] showed that key details associated with As adsorption and termination of Ge, such as dimer orientation, as well as the surface step structure can be differentiated using RAS by careful experiments and complementary STM, XPS, and low-energy electron diffraction (LEED) characterization, as shown in Figure 29.18.…”
Section: Reflectance Anisotropy Spectroscopymentioning
confidence: 96%
“…Temperature-dependent measurements showed sensitivities of 10 17 /cm 3 at 400 C to 1 Â 10 18 /cm 3 at 600 C [42]. Recent work has also shown that RAS can be used to monitor the hydrogen termination of Ge during annealing in N 2 (Figure 29.19) [45]. Recent work by Bruckner et al [44] showed that key details associated with As adsorption and termination of Ge, such as dimer orientation, as well as the surface step structure can be differentiated using RAS by careful experiments and complementary STM, XPS, and low-energy electron diffraction (LEED) characterization, as shown in Figure 29.18.…”
Section: Reflectance Anisotropy Spectroscopymentioning
confidence: 96%
“…While there have been many RAS studies of Si(001) surfaces, there have been very few studies of Ge(001), with recent work focusing on in situ MOVPE studies, where RAS has unique advantages. [8][9][10][11] Regarding calculations of the spectral response, the situation is similar. Recently, we have calculated the optical response of some Si(001) and Ge(001) surfaces using a local-orbital-based hybrid density functional theory (DFT) approach.…”
mentioning
confidence: 89%
“…12 The experimental optical spectra from different studies are very similar, all having a minimum in the range of 1.8-2.0 eV, another minimum at 3.0 eV, and maxima around 2.2 and 4.2 eV, the E1 and E2 critical points of bulk Ge. 9,10 The calculated optical response for the c(4 Â 2) and p(2 Â 2) structures, using the hybrid DFT approach, is compared with the experiment in Fig. 2, where it can be seen that the spectral lineshape is well reproduced, although the reduced intensity of the $2 eV peak observed results in an almost entirely negative-going experimental spectrum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure ) . This enabled in situ studies on the preparation of clean and monohydride terminated Ge(100) surfaces and the H desorption kinetics in MOVPE ambient, respectively . From DFT calculations and comparison to experimental results, however, the microscopic origin of the RA spectra could not yet be clarified due to lack of low temperature RAS data.…”
Section: Epitaxial Reference Surfacesmentioning
confidence: 99%